The effects of thymoquinone and artificial light exposure on rat fertility - Syazana binti Mohamad Zahri (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2018)
Infertility is a common reproductive disorder in both men and women. Urban lifestyle has compelled people to consume excessive and unnecessary supplements and also caused disruption of sleep cycle which resulted in unhealthy lifestyle that can cause the society to be infertile. Moreover, the battery of invasive diagnostic tests has relatively deterred men from seeking assistance and treatment for their infertility issues. A rapid and reliable test making use of non-invasive samples will be sought by both patients and clinicians alike. The purpose of the study was to observe the effects of subchronic thymoquinone administration and prolonged artificial light exposure to Sprague-Dawley rats. This also includes detection of testosterone as male fertility biomarker from non-invasive samples using paper-based lateral flow assay (PLFA) strip with smartphone usage. Adult male Sprague-Dawley rats were equally divided into six groups (n=6). One group was used as a negative control with no intervention. The positive control group was treated with corticosterone (10 mg/kg) for 10 successive days, followed by a single dose of cisplatin (10 mg/kg), all prior to the day of sacrifice. The next three groups were given thymoquinone via intraperitoneal route at doses of 5 mg/kg, 10 mg/kg and 30 mg/kg, twice a week. The final group was exposed to a 24 hours cycle of artificial fluorescent light to induce stress. All the interventions were given within a 56 days period including sampling of blood, saliva and urine at day 0 and day 56 respectively All the animals were sacrificed at day 56 to harvest the testes. Testosterone and corticosterone hormone levels in the blood, saliva and urine were measured using enzyme-linked immunosorbent assay (ELISA) kit. Sperm analysis parameters were measured followed by a histological assessment of the testes using haematoxylin and eosin (H&E) stain. Paper-based lateral flow assay strip was then developed based on the colour change from antigen-antibody reaction on paper which reflects the testosterone levels from urine samples. The colour change was captured using a smartphone camera and an applications that captured the RGB colour value. The results were then compared with ELISA test data. The results showed that the thymoquinone supplementation at 30 mg/kg subchronically can reduce the testosterone level and thus affecting fertility (p<0.05). Meanwhile, in the 24-hour light exposure group, no significant effect of reduced fertility or increasing stress were detected compared to controls. The B value from RGB colour was chosen to measure the testosterone as it have higher correlation (r2=0.98) than R and G value. This testosterone level assessment using the paper-based colourimetric test produced comparable data with ELISA result. Therefore, this sensor holds the potential of testing infertility in men more efficiently using non-invasive samples while at the same time increasing compliance in the sampling approach.